Lower Limb Power and Eye–Foot Coordination as Determinants of Shooting Performance in Youth Soccer - M. Zulhairi; Raffly Henjilito (INSPIRETECH GLOBAL INSIGHT & (ISORI KAMPAR), 2026)
Purpose of the study: This study aimed to examine the contribution of leg muscle power and eye-foot coordination to shooting skills among athletes of UIR Soccer School (USS) Club Under 17. Materials and methods: This study adopted a correlational research design using multiple correlation analysis. The population and sample comprised 15 male athletes of USS Under 17, recruited through total sampling. Data were collected using the Standing Long Jump Test for leg muscle power, the Eye-Foot Coordination Test (Winarno, 2006), and the Shooting at the Ball Test. Pearson product-moment correlation and multiple correlation coefficients were computed using standard statistical formulas. Results: Results revealed that: (1) leg muscle power contributed 62.41% to shooting skills (r = 0.79 > rₜₐᵇₗₑ = 0.514); (2) eye-foot coordination contributed 42.25% (r = 0.65 > 0.514); (3) the combined contribution of leg muscle power and eye-foot coordination to shooting skills was 44.89% (R = 0.67 > 0.514). Conclusions: Both leg muscle power and eye-foot coordination significantly contribute to shooting performance in youth soccer players. Training programs should prioritize explosive strength and eye-foot coordination exercises to enhance shooting effectiveness.